Improving Perspective-Taking, Fantasy, Personal Distress and Empathic Accuracy of Students through the Socratic Dialogue Methods - Murdianto Murdianto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2020)
Four elements of empathy are perspective-taking, fantasy, personal distress, and emphatic accuracy. Empathy is essential for people, especially for those who will work as helpers, such as teachers, counselors, nurses, doctors, and other similar professions. This paper studies and measures the effectiveness of the Socratic dialogue method used to increase four elements of student's empathy. This experimental study uses a pretest-posttest control group design. Nineteen participants were selected and divided into the experimental and control group. The experimental results were analyzed by a one-way ANOVA and t-test using SPSS 20.0 for Windows. The results indicate that Socratic dialogue is effective in improving four elements of empathy. Keywords: empathy, learning model, pre-service education, the Socratic dialogue method, teacher candidates. Empat elemen empati adalah perspective-taking, fantasy, personal distress, dan emphatic accuracy. Empati penting bagi individu, khususnya bagi mereka yang akan bekerja sebagai helper, seperti guru, konselor, perawat, dokter dan profesi sejenis. Penelitian ini menguji efektifitas metode dialog Socratic untuk meningkatkan empati mahasiswa. Penelitian eksperimen ini menggunakan pretest-posttest control group design. 19 partisipan terpilih dan dibagi dalam kelompok eksperimen dan kelompok kontrol. Hasil eksperimen ini dianalisis dengan uji anova satu jalan dan uji-t, dengan bantuan program SPSS release 20.0 for windows. Hasil penelitian ini menunjukkan bahwa metode dialog Socratic efektif dalam meningkatkan empati mahasiswa. Kata kunci: calon guru, empati, metode dialog Socratic, model pembelajaran, pendidikan prajabatan..